Planning for the Construction of School Buildings and School Facilities for SMPN 1 Padangan - Sujiat Sujiat (Edumaspul: Jurnal Pendidikan, 2025)
Planning for high-rise buildings is an important aspect in the development of an area. As the rapid population growth continues, the need for housing and public facilities is increasing. Planning a high-rise building for a school is urgently needed today considering the increasing number of students and the need for school facilities in an area. Padangan Village is a village in the western part of Bojonegoro Regency and is the location of SMPN 1 Padangan which at this time is in dire need of a school building and facilities to meet and support the needs of students in the school. The results of the analysis with sap 2000 are planned Sloof (S1) is planned using the dimension of 25x50 with reinforcement 5D16 and the Main Beam (B1) is planned using the dimension of 30 x 55 with reinforcement 5D16, the column is planned using the dimension of 45x45 with reinforcement 12 D16 mm with a transverse reinforcement distance of 2 Ø10-100 mm. Floor plates are planned using two-way concrete plates with a thickness of 12 cm. For x-direction focal reinforcement use Ø10-85 mm, x-direction field reinforcement uses Ø10-130 mm, y-direction focal reinforcement uses Ø10-85 mm and y-direction field reinforcement uses Ø10-130 mm.